2002
DOI: 10.1046/j.1537-2995.2002.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of WBC reduction of transfused RBCs on postoperative infection rates in cardiac surgery

Abstract: No evidence has been found, analyzed by intention to treat, that use of WBC-reduced, BCD, or WCF RBCs reduces postoperative inpatient infection in patients undergoing cardiac bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
172
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(180 citation statements)
references
References 25 publications
8
172
0
Order By: Relevance
“…Through all randomized controlled trials only in cardiac surgery the findings were conclusive for a deleterious TRIM effect of WBC-containing RBCs with a higher short-term (up to three month post transfusion) mortality rate [69], [70], [71]. Though, even in this setting, the reasons for the excess deaths attributed to WBC-containing ABTs remain elusive.…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 96%
“…Through all randomized controlled trials only in cardiac surgery the findings were conclusive for a deleterious TRIM effect of WBC-containing RBCs with a higher short-term (up to three month post transfusion) mortality rate [69], [70], [71]. Though, even in this setting, the reasons for the excess deaths attributed to WBC-containing ABTs remain elusive.…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 96%
“…Four cardiac surgery RCTs have been published [31][32][33][34] and 2 other cardiac surgery studies are available only as abstracts and contain limited data [35,36]. The primary methods and results are shown in the Table 1.…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%
“…Subgroup analysis showed that the mortality rate was only higher in the patients that received >3 RBC units in the BCD-RBC group than in the filtered RBC group. Wallis et al [32] conducted a study using 3 types of blood products: filtered whole blood (stored <7 d before filtration), BCD-RBC, and plasma-reduced RBCs. Postoperative mortality at 3 months was 0.5%, 2.9%, and 2.5%, respectively (p=0.2), indicating no additional deleterious effect of the greater number of leukocytes in plasmareduced RBCs, as compared to BCD-RBCs [32].…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%
See 2 more Smart Citations